Analisis Keputusan Membeli Berbasis Brand Awareness sebagai Impak Google Ads dan Facebook Ads (Kajian Pelanggan Lazada) - Bertinus Sijabat (Ridwan Institute, 2021)
This research aims to test Brand Awareness Based Buying Decision Analysis as an Impact on Google Ads and Facebook Ads. The study was conducted on 97 respondents who are Lazada customers. The results of this study showed: 1). Google Ads variable (X1) with Brand Awareness (Y1) proved to have an effect and significant effect on Brand Awareness, with a parameter coefficient of 0.5081 (P Value <0.05) of 0.0000. This indicates that google ads variables have a significant effect on Brand Awareness (Y1) variables. 2). The Facebook Ads variable (X2) with Brand Awareness (Y1) proved to be influential and significant to Brand Awareness, with a parameter coefficient of 0.3447 and a P Value < of 0.05 of 0.0000. This indicates that the Facebook Ads variable affects the Brand Awareness (Y1) variable. 3). The Google Ads variable (X1) with the Purchase Decision (Y2) proved significant effect on the Buying Decision with a parameter coefficient of 0.2385 and P Value < of 0.05 of 0.0009. This suggests that Google Ads variables have an effect on buying decision variables (Y2). 4). The Facebook Ads variable (X2) with the purchase decision (Y2) proved to have an effect and significant effect on the buying decision i.e. with a parameter coefficient of 0.2761 and P Value < of 0.05 of 0.0020. This indicates that the Facebook Ads variable affects the buy decision variable (Y2). 5). Variable Brand Awareness (Y1) with the decision to buy (Y2) proved influential and significant to the Buying Decision with a parameter coefficient of 0.4497 and P Value < 0.05 of 0.0000. This indicates that the Brand Awareness variable is proven to have an effect on the Buying Decision (Y2) variable.